2014
DOI: 10.3390/min4020293
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Acid-Generating and Metal Leaching Potential of a Sub-Arctic Oil Shale

Abstract: Shales are increasingly being exploited for oil and unconventional gas. Exploitation of sub-arctic oil shales requires the creation of gravel pads to elevate workings above the heaving effects of ground ice. These gravel pads can potentially generate acidic leachate, which can enhance the mobility of metals from the shale. To examine this potential, pyrite-bearing shale originating from sub-Arctic gravel pad sites were subjected to leaching tests for 600 days at initial pH values ranging from 2 to 5, to simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…XRF was one of the techniques used by Tremain et al 213 to analyse char created from coal tailings sourced from two Australian coal mines. Concerning a related topic, Mumford et al 218 were concerned about the potential for acidic leachate from pyrite-bearing gravel pads that are required to elevate workings in the exploration of sub-arctic oil shales above the heaving effects of ground ice. Wang et al 214 investigated the recovery of vanadium by otation from low-grade stone coal, measuring the mineral composition and microstructure of the source material using the XRF, XRD and SEM techniques.…”
Section: Industrial Minerals and Consequences From Mining Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…XRF was one of the techniques used by Tremain et al 213 to analyse char created from coal tailings sourced from two Australian coal mines. Concerning a related topic, Mumford et al 218 were concerned about the potential for acidic leachate from pyrite-bearing gravel pads that are required to elevate workings in the exploration of sub-arctic oil shales above the heaving effects of ground ice. Wang et al 214 investigated the recovery of vanadium by otation from low-grade stone coal, measuring the mineral composition and microstructure of the source material using the XRF, XRD and SEM techniques.…”
Section: Industrial Minerals and Consequences From Mining Activitymentioning
confidence: 99%
“…The conclusions of this investigation were that the clay layer liners containing contaminants had been breached over time due to overloading of the pits and/or structural damage, allowing chemical materials to permeate into the environment and into aquifers. Concerning a related topic, Mumford et al 218 were concerned about the potential for acidic leachate from pyrite-bearing gravel pads that are required to elevate workings in the exploration of sub-arctic oil shales above the heaving effects of ground ice. They used the TXRF technique to analyse small liquid samples withdrawn from the pads and reported that there was signicant potential for the leachate to contain Cu, Fe, Mn, Ni, S and Zn.…”
Section: Industrial Minerals and Consequences From Mining Activitymentioning
confidence: 99%
“…Dold [5] reviews the complex biogeochemical and mineral dissolution processes in sulfidic mine tailings leading to the formation of acid mine drainage (AMD). Mumford et al [6] and Langman et al [7] describe long-term acid generation from sub-Arctic oil shales and waste rock from the Diavik Diamond Mine in the Northwest Territories of the Canadian Arctic, respectively. In both cases, the acid generation potential is dependent on the concentrations of sulfide, neutralization reactions with carbonates and Al-bearing minerals and temperature.…”
mentioning
confidence: 99%